Serum immune indicators including IgM, IgA, and IgG levels and quality of life of patients with gastrointestinal tumours during chemotherapy - Wan Mengchao; Wang Yunlong; Zeng Lin; Zhou Zhiyong; Yao Weirong (Journal of Medical Biochemistry)
Background: Patients with gastrointestinal tumours often experience malnutrition and compromised immune function during chemotherapy, leading to a significant decline in quality of life. This study aimed to evaluate the effects of dietary nursing interventions on the nutritional status, immune function, and quality of life in patients undergoing chemotherapy. Methods: A total of 100 patients with gastrointestinal tumours receiving chemotherapy from January 2023 to June 2024 were randomly divided into two groups: a control group (CG) and a study group (SG). Both groups received conventional nursing interventions, but the SG also received dietary nursing interventions focused on personalized nutrition, dietary habits, and gastrointestinal health. Nutritional status was assessed using body mass index (BMI), haemoglobin (HGB), serum albumin (ALB), and oral mucosal cell apoptosis rate. Immune function was evaluated by measuring immunoglobulin M (IgM), immunoglobulin A (IgA), and immunoglobulin G (IgG) levels. Quality of life was measured using the GQOL-74 scale. Results: After the nursing interventions, the SG showed significant improvements in BMI, HGB, ALB, and oral mucosal cell apoptosis rate compared to the CG (P<0.05). Additionally, IgM, IgA, and IgG levels were significantly higher in the SG (P<0.05). Quality of life scores, including physical, social, psychological, and material life, also improved significantly in the SG compared to the CG (P<0.05). Conclusions: Dietary nursing interventions significantly improved the nutritional status, immune function, and quality of life of patients with gastrointestinal tumours undergoing chemotherapy. These findings underscore the importance of incorporating dietary care into nursing practices for cancer patients to support their overall well-being and treatment outcomes.